An Expository Study Of The Right Of Children To Health Under The Shari'ah And Nigerian Law - Abdulraheem Taofeeq Abolaji
Right to health is the bedrock of all other rights. As a member of the international community, Nigeria is committed to protecting the rights of its citizens, especially the children to have access to adequate healthcare by adopting, ratifying and domesticating the Convention on the Rights of the Child and enacting the Child's Rights Act, 2003. Section 13 of the Act clearly requires both the government and parents to ensure the provision of basic health facilities for the treatment and welfare of children and ensuring that the children enjoy health benefits. Notwithstanding the provision of Section 13 of the CRA. Nigerian children still suffer prevalently from diseases because of inadequate health facilities and medical experts to attend to their medical needs. One of the greatest challenges facing the health system in Nigeria is in the area of child health. According to World Health Organization, Nigeria is among the five countries that contribute 50% to the annual global mortality among infants and children under five - years of age as a result of several epidemic diseases like malaria, pneumonia, measles, diarrhoea, malnutrition and inadequate immunization. Meanwhile, Nigeria has a majority of Muslims who constitute about 51% of the population. One of the challenges facing the adequate implementation of the provisions of CRA 2003 including Section 13 is the disagreement of some Muslims with the principles of the CRA 2003 on the grounds that its provisions contravene fundamental principles of the Shari 'ah, including the maqasid al-Shari'ah. This study, therefore, examines the extent to which the right of children to health is protected under both the Shari'ah and the Nigerian legislation. The study also investigates whether there are any conflicts between the provisions of both Shari'ah and the Nigerian law regarding the protection of children's health. The study similarly finds out the factors that contribute to the ineffective implementation of the protection of children's right to health in Nigeria. The study was designed as a qualitative research that draws from analysis of data taken from doctrinal research into primary and secondary legal sources as well as unstructured interviews. The study also engaged in comparative analysis of principles of Shari ah and the CRA 2003 on rights of children. The study finds that Shari'ah fully recognises the right of children to health as part of the Maqasid al-Shari 'ah. The study also finds that the provision of the CRA 2003 has not been effectively implemented in Nigeria due to several social, cultural, religious, political and legal factors. The study concludes that there is a need to recognise child's right as an absolute right under the Nigerian Constitution by removing the ouster clause in place against Chapter I1 ofthe Constitution. The study proposes several ways forward like harmonisation between the provisions of Shari'ah and the CRA 2003.